ORDER VOL.1 (Baltic International Yearbook of Cognition, Logic and Communication, 2005)
Contains the table of contents of the first volume of the Baltic Intentational Yearbook of Cognition, Logic and Communication, originally published on paper medium (University of Latvia Press, 2005).